PENGARUH PEMANFAATAN LAHAN TERHADAP EKOSISTEM PESISIR DI KAWASAN TELUK AMBON - Asyiawati, Yulia (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2010)
This study aims (1) to analyzing the shift in utilization patterns compared with the carrying capacity and land suitability; (2) to analyze the status of coastal ecosystems. The method of analysis used in this study is the analysis of Geographic Information System (GIS).The results showed that there was a shift utilization, namely: to change the function of protected areas into mixed areas and dryland farming for 83.12%, coastal border that changes the function into the airport area, mixed area, settlements, dry land farming for 96.02%, dry land agriculture which transformed the function into neighborhoods, the area is a mixture of 8.70%. This resulted in the status of coral reef ecosystems, including criteria for medium-well with percentage coral cover ranged from 36.63 to 75.62%, the status of mangrove ecosystems including the category tree density was 780 to 1420 trees / ha, and the status of seagrass ecosystems, including categories less rich with the percentage cover ranged from 33.13% to 44.39%.